William Bebb papers - Bebb, William, 1802-1873.
Autograph letters and clipped signatures from an album started for Bebb by his father, Edward Bebb, and Samuel Roberts, Welsh political reformer and founder of a settlement in Tennessee. Includes autographs of British politicians, military leaders, authors, and missionaries, among them John Bright, Thomas Babington Macaulay, Sir Francis Palgrave, Sir Robert Peel, and Henry Richard. Letters collected by William Bebb himself include of John Quincy Adams, John C. Calhoun, Alexander James Dallas, Charles Hammond, William Henry Harrison, William Hull, Andrew Jackson, Thomas Jefferson, James Winchester, and Thomas Worthington. William Bebb's own correspondents include John Brough, Thomas Corwin, Thomas Ewing, Seabury Ford, Horance Greeley, John McLean, Samuel Finley Vinton, James Whitcomb, and John C. Wright. Many letters relate to Ohio and Whig politics.
Educator, lawyer, and governor of Ohio.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Bebb, Edward; Bright, John, -- 1811-1889 -- Correspondence; Brough, John, -- 1811-1865 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Corwin, Thomas, -- 1794-1865 -- Correspondence; Dallas, Alexander James, -- 1759-1817 -- Correspondence; Ewing, Thomas, -- 1789-1871 -- Correspondence; Ford, Seabury, -- 1801-1855 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Hammond, Charles, -- 1779-1840 -- Correspondence; Harrison, William Henry, -- 1773-1841 -- Correspondence; Hull, William, -- 1753-1825 -- Correspondence; Jackson, Andrew, -- 1767-1845 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Macaulay, Thomas Babington Macaulay, -- Baron, -- 1800-1859 -- Correspondence; McLean, John, -- 1785-1861 -- Correspondence; Palgrave, Francis, -- Sir, -- 1788-1861 -- Correspondence; Peel, Robert, -- 1788-1850 -- Correspondence; Richard, Henry, -- 1812-1888 -- Correspondence; Roberts, Samuel, -- 1800-1885.; Vinton, Samuel Finley, -- 1792-1862 -- Correspondence; Whitcomb, James, -- 1795-1852 -- Correspondence; Winchester, James, -- 1752-1826 -- Correspondence; Worthington, Thomas, -- 1773-1827 -- Correspondence; Wright, John C. -- 1783-1861 -- Correspondence; Whig Party (U.S.); Authors, English -- Autographs; Autographs; Missionaries -- Great Britain -- Autographs; Politicians -- Great Britain -- Autographs; Statesmen -- United States -- Autographs; Great Britain -- Armed Forces -- Officers -- Autographs; Ohio -- Politics and government -- 19th century; Educators; Governors -- Ohio; Lawyers